2018
DOI: 10.1016/j.avb.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of men's sexual violence perpetration and sexual risk behavior: A literature review

Abstract: According to the Confluence Model of Sexual Violence, men with a strong impersonal sex orientation (i.e., greater engagement in sexual activities with more casual sexual partners) are at increased risk of perpetrating sexual violence. Research from a variety of countries and samples has supported this proposition, finding that men who perpetrate sexual violence are also more likely to engage in risky sexual behavior. The present article reviews this literature, synthesizing research findings from both psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 95 publications
4
45
0
1
Order By: Relevance
“…One previous study analyzed the data of five cross-national surveys that were conducted among school aged children. The findings showed that, in four of the surveys, males were more likely to become victims of a bully and in one of the online survey; bullying prevalence was high among girls [30]. However, this finding might vary across schools, communities, countries, and cultures [9].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One previous study analyzed the data of five cross-national surveys that were conducted among school aged children. The findings showed that, in four of the surveys, males were more likely to become victims of a bully and in one of the online survey; bullying prevalence was high among girls [30]. However, this finding might vary across schools, communities, countries, and cultures [9].…”
Section: Discussionmentioning
confidence: 88%
“…Supporting this evidence, previous studies have emphasized the requirements of appropriate anti-bullying programs at schools [40][41][42][43][44][45]. It is therefore likely that learning outcomes could be improved through antischool bullying strategies like school/classroom rules and policies, curriculum materials, parents/teachers trainings and meetings, disciplinary methods and improved playground supervision [46,47].…”
Section: Mental Health Behaviorsmentioning
confidence: 90%
“…Men higher in sexual risk behavior are also more likely to be aggressive (for a review, see Davis, Neilson, Wegner, & Danube, 2018). Sexual risk behavior refers to any sexual behavior that increases one's risk of a negative health outcome, such as contracting or transmitting an infection or experiencing unwanted pregnancy (Davis, Neilson, et al, 2018). One behavior that represents the nexus of sexual risk and violence is coercive condom use resistance (CUR).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated that 42% of nonproblem drinking men have utilized at least one coercive CUR tactic since adolescence (Davis, 2018). Due to its conceptual and behavioral overlap with sexual aggression (Davis, Neilson, et al, 2018), coercive CUR is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…After controlling for age and number of lifetime sexual partners, the severity of women's sexual victimization history was positively associated with receiving and using both coercive and non-coercive condom use resistance. Although other studies have demonstrated that men's history of perpetrating sexual assault is associated with resistance to condom use and use of force to obtain condomless sex (see Davis, Neilson, Wegner, & Danube, 2018 for a review), this is the first investigation documenting the association of sexual assault history and condom use resistance in women. Previous studies have documented that sexually victimized women are more likely than nonvictims to engage in a variety of sexually risky behaviors, such as inconsistent condom use and having a higher numbers of sexual partners (Senn et al, 2008).…”
Section: Discussionmentioning
confidence: 88%